Dysregulation of MicroRNA-34a Expression in Head and Neck Squamous Cell Carcinoma Promotes Tumor Growth and Tumor Angiogenesis - Kumar, Bhavna (Public Library of Science, 2012)
BACKGROUND: MicroRNAs (miRs) are small non-coding RNAs that play an important role in cancer development where they can act as oncogenes or as tumor-suppressors. miR-34a is a tumor-suppressor that is frequently downregulated in a number of tumor types. However, little is known about the role of miR-34a in head and neck squamous cell carcinoma (HNSCC). METHODS AND RESULTS: miR-34a expression in tumor samples, HNSCC cell lines and endothelial cells was examined by real time PCR. Lipofectamine-2000 was used to transfect miR-34a in HNSCC cell lines and human endothelial cells. Cell-proliferation, migration and clonogenic survival was examined by MTT, Xcelligence system, scratch assay and colony formation assay. miR-34a effect on tumor growth and tumor angiogenesis was examined by in vivo SCID mouse xenograft model. Our results demonstrate that miR-34a is significantly downregulated in HNSCC tumors and cell lines. Ectopic expression of miR-34a in HNSCC cell lines significantly inhibited tumor cell proliferation, colony formation and migration. miR-34a overexpression also markedly downregulated E2F3 and survivin levels. Rescue experiments using microRNA resistant E2F3 isoforms suggest that miR-34a-mediated inhibition of cell proliferation and colony formation is predominantly mediated by E2F3a isoform. In addition, tumor samples from HNSCC patients showed an inverse relationship between miR-34a and survivin as well as miR-34a and E2F3 levels. Overexpression of E2F3a completely rescued survivin expression in miR-34a expressing cells, thereby suggesting that miR-34a may be regulating survivin expression via E2F3a. Ectopic expression of miR-34a also significantly inhibited tumor growth and tumor angiogenesis in a SCID mouse xenograft model. Interestingly, miR-34a inhibited tumor angiogenesis by blocking VEGF production by tumor cells as well as directly inhibiting endothelial cell functions. CONCLUSIONS: Taken together, these findings suggest that dysregulation of miR-34a expression is common in HNSCC and modulation of miR34a activity might represent a novel therapeutic strategy for the treatment of HNSCC.